FRI0488 Insufficient immunosuppressive use is the leading cause of vascular relapses in behcet's disease. (12th June 2018) - Aksoy, A.; Alibaz Öner, F.; Ergun, T.; Direskeneli, R.H.
Abstract : Background: Vascular involvement is observed in up to 40% in Behcet Disease (BD) patients, as an important cause of mortality and morbidity, especially for males (Kural-Syahi E et al, 1984). Objectives: Purpose of this study is to describe clinical-demographic properties, treatments and prognosis of vascular BD patients in a tertiary rheumatology clinic. Methods: BD patients fullfilling ISG 1990 criteria are recruited from the multi-disciplinary Behcet's Clinic in Marmara University, Istanbul for this retrospective study. All data is collected from patient files (ISG for BD, 1990). Results: Mean age of BD patients (M/F:102/22) was 29.3±7.3 years at diagnosis and 32.4±9.5 years old during first vascular event. Median follow up was 47 17–71 months. Mean age of female patients was significantly older during first vascular event (table 1). 73.2% of vascular involvement was venous, mostly deep vein trombosis (table 2). 32% (n=40) of patients presented first with a vascular event and diagnosed as BD. Twenty (16%) patients were diagnosed with a median of 12 1–120 months after the first vascular event. 15 (6.5%) patients were using immunsupressive (IS- mainly azatiopirin) drugs either for resistant mucocutaneous symptoms or major other organ involvement during the first vascular event. Vascular relaps rate was 40.7% and it was similar between sexes (F: 33.3% vs M: 42.2%, p=0.6). After the first vascular event, 96 (85.7%) patients had been treated with ISs and 58.9% used anticoagulants. Median IS and anticoagulant usage duration was 25.5 (5–48) and 2 (0–12) months respectively. Relaps rate was higher in patients who had stopped ISs (87.5% vs 32.3%). IS treatment duration was shorter at relapsing patients (44 vs 64 months, p=0.001). Smoking rate was higher at male patients but no association was observed with vascular relapses. IVC: inferior vena cava, PAA: pulmoner arter aneurysmeı, PAT: pulmoner arter trombus, SVC: superior vena cava Conclusions: Our results show that female BD patients have a vascular event at a later age compared to males, but the course of vascular disease is not influenced with gender. Early termination of immunosupressive treatments seems to be the most important cause of vascular relapses Disclosure of Interest: None declared